Pelaksanaan Program Pendidikan Anak Usia Dini Holistik dan Terpadu dalam Pencegahan Stunting di Kabupaten Aceh Tamiang - Ulfa Rismaya Putri; Diana Diana; Ali Formen (Postgraduate, University of Mataram, 2026)
Stunting remains a major public health issue in Indonesia due to its long-term effects on children’s growth, cognitive development, and future productivity. Despite government efforts, the implementation of integrated stunting prevention programs at the early childhood education level remains inconsistent. This study aims to analyze the implementation of the Holistic Integrative Early Childhood Education (HI-ECE) program in preventing stunting in Aceh Tamiang Regency. A qualitative case study approach was employed involving 30 participants consisting of early childhood educators, principals, health workers, village officials, and parents from two early childhood education centers. Data were collected through in-depth interviews, observations, and document analysis. The data were analyzed using the interactive model of data reduction, data display, and conclusion drawing, supported by triangulation to ensure data credibility. The results show that educational services are the most consistently implemented component, particularly through the integration of hygiene, health, and nutrition awareness into daily learning activities. However, health, nutrition, caregiving, and child protection services remain limited and depend largely on external programs. Weak cross-sectoral coordination, limited human resources, and inconsistent parental participation hinder effective implementation. The study concludes that strengthening institutional capacity, formalizing intersectoral collaboration, and increasing parental engagement are essential to optimize early childhood education institutions as convergence points for sustainable stunting prevention